Proses Transaktif, Interaksi Antar Aktor Agen Transfer dalam Pembangunan Lokal - Muhammad Taufiq; Suhirman Suhirman; Benedictus Kombaitan (Diponegoro University, 2020)
Planning as a decision-making tool got intervention from the actors involved in it, through deliberation which is transactive planning and face-to-face dialogue between planners as transfer agents and the community. This situation has resulted in a mismatch between the priority policies for using the budget set at the local level and the implementation guidelines set by the central government. Questions arise how interactions between actors occurred in a transactive process. This article evaluates the interaction between involved actors in the transactive process, which occurs during a practice of local development planning program activity. Evaluations were carried out on village fund program cases in Indonesia, through qualitative approach analysis. The study aims to provide an understanding of the interactions between transfer agent actors during deliberation at the local level. The results show that the interaction between transfer agents conduct through the practice of dominating ideas, which tend to emphasize the dominance of certain parties in prioritizing budget use policies.